Awards: Thank you for your nominations! - ORNAC (Operating Room Nurses Association of Canada Journal, 2025)
The ORNAC Awards Committee would like to extend a heartfelt thank you to everyone who took the time to nominate a colleague for a 2025 ORNAC Award. Your nominations recognize the dedication, leadership, and excellence of perioperative nurses across Canada and celebrate their contributions to our profession.